Experimental investigation of cracking behaviors of ductile and brittle rock-like materials (Fracture and Structural Integrity, 2021)
The cracking characteristics of ductile rocks were studied by similar materials with sand, barite, epoxide resin, polyamide, silicone rubber and alcohol, while the cracking characteristics of brittle rocks were investigated by similar material with sand, barite, rosin and alcohol. In this paper, to enhance the application range of the rock-like materials in the field of geotechnical engineering model tests, the values of the elastic modulus and the compressive strength of the artificial rock-like materials are changed in a wide range by adjusting the amount of cementitious materials (epoxide resin, polyamide, rosin, etc). The elastic modulus, compressive strength and cracking characteristics were obtained from the complete axial stress–strain curves of the specimens made of similar materials, which were cast using the different mixture ratios. These experimental data can provide quantitative investigation on mixture ratios of similar materials of rocks to model the geotechnical engineering. Furthermore, the effect of mixture ratios on mechanical properties and crack propagation pattern of specimens were also investigated by the specimens with pre-existing flaws under uniaxial compressive tests
Keywords: Rock-like materials; Material composition; Ductility; Brittleness; Crack evolution